2020
DOI: 10.1159/000510769
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Patients with Hematologic Disorders Undergoing Therapy: Perspective of a Large Referral Hematology Center in Rome

Abstract: Introduction: Patients with cancer may be more susceptible to and have higher morbidity and mortality rates from COVID-19 than the general population, while epidemiologic data specifically addressed to hematologic patients are limited. To investigate whether patients with hematologic diseases undergoing therapy are at increased risk for acquiring SARS CoV-2 infection compared to the general population, a retrospective study was carried out at a referral hematologic center in Rome, Italy, during the period of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The authors present their own experiences with treating patients with hematologic diseases and COVID-19 infection obtained in a single center for specialized hematology care in the Czech Republic in 2020. In a study by Girmenia et al, 13 the prevalence of COVID-19 among patients with hematologic diseases (including nonmalignancies) was 0.24%, as compared with only 0.12% in the general population ( P = .14). Other studies reported prevalence rates of 0.17% to 0.9%, depending on the type of hematologic malignancy.…”
Section: Discussionmentioning
confidence: 90%
“…The authors present their own experiences with treating patients with hematologic diseases and COVID-19 infection obtained in a single center for specialized hematology care in the Czech Republic in 2020. In a study by Girmenia et al, 13 the prevalence of COVID-19 among patients with hematologic diseases (including nonmalignancies) was 0.24%, as compared with only 0.12% in the general population ( P = .14). Other studies reported prevalence rates of 0.17% to 0.9%, depending on the type of hematologic malignancy.…”
Section: Discussionmentioning
confidence: 90%
“…There is a dearth of published literature on outcome of SARS-CoV-2 infected children with various comorbidities [8][9][10][11]. Three children with disseminated tuberculosis developed acute respiratory distress syndrome (ARDS) and multi-organ failure syndrome (MODS), and one died due to raised intracranial tension with neurogenic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, planned activities were suspended, except for non-deferrable treatments, including those for patients with haematological malignancies. 2 …”
Section: Introductionmentioning
confidence: 99%